3-D distribution characteristics of the micro-defects in the PEO coating on ZM6 mg-alloy during corrosion. (September 2020) - Chen, Zhenning; Ji, Haotian; Geng, Xiaoqian; Chen, Xiaochun; Yong, Xingyue; Zhang, Suode
Graphical abstract: Highlights: The quantitative distribution of micro-defects in the PEO coating was detected by X-ray tomography. The sizes, shapes, and numbers of the micro-defects changed greatly with immersion time compared with that in the pristine PEO coating. The open-pores grew continuously, and then connected with the surrounding micro-pores, finally forming through-pores in the PEO coating. The corrosive media reached the coating/substrate interface through the through-pores, resulting in the corrosion of the substrate. Abstract: The 3-D distributions of the micro-defects in the PEO coating on ZM6 Mg-alloy were investigated using X-ray tomography (XRT) and confocal laser scanning microscopy (CLSM) in conjunction with scanning electron microscopy (SEM). The results showed that micro-defects with different sizes and shapes existed in the pristine PEO coating. The sizes, shapes, and numbers of micro-defects of the PEO coating in 3.5 % NaCl solution changed greatly with immersion time under the synergistic effects between corrosion and the extension of corrosion products. Finally, the through-defects were formed by connecting the adjacent micro-defects and the substrate corroded.